Genetic breakthroughs in the Brassica napus–Sclerotinia sclerotiorum interactions - Chen, Rong-Shi; Wang, Ji-Yi; Sarwar, Rehman; Tan, Xiao-Li (Frontiers in Plant Science, 2023)
Sclerotinia sclerotiorum (Lib.) de Bary is a highly destructive fungal pathogen that seriously damages the yield and quality of Brassica napus worldwide.The complex interaction between the B. napus and S. sclerotiorum system has presented significant challenges in researching rapeseed defense strategies. Here, we focus on the infection process of S. sclerotiorum, the defense mechanisms of rapeseed, and recent research progress in this system. The response of rapeseed to S. sclerotiorum is multifaceted; this review aims to provide a theoretical basis for rapeseed defense strategies.